Enhancing Students' Problem-Solving Skills through Ethnomathematics-Based Geometry Learning with an Android Mobile Application - Hodiyanto; Erna Setyaningsih; Buaddin Hasan; Markus Palobo; Bidya Nath Koirala (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
Despite the growing integration of technology in mathematics education, research on mobile learning platforms embedding local cultural contexts—particularly ethnomathematics—remains limited at the junior secondary level in Indonesia. Mathematical problem-solving ability remains a persistent challenge among students, necessitating Android-based learning media as a more engaging instructional solution. This investigation examined the extent to which an Android-based interactive mobile learning (m-learning) platform, integrated with ethnomathematics derived from Pontianak's local culture. A quasi-experimental posttest-only control-group design was adopted for this purpose. From nine classes at SMP Negeri 2 Pontianak, 60 participants were selected via cluster random sampling—30 in the experimental group receiving m-learning instruction and 30 in the comparison group receiving instruction without m-learning. Assessment of mathematical problem-solving capacity was conducted through a descriptive test comprising three items structured around Polya's four-stage indicators, with empirically established validity coefficients ranging from 0.94 to 0.96 and a reliability coefficient of 0.78. Statistical examination involved a one-tailed independent samples t-test for group comparison, supplemented by Cohen's d for effect size quantification. Findings revealed that learners exposed to m-learning instruction demonstrated substantially superior mathematical problem-solving performance compared to their counterparts in the conventional group (mean = 84.67 vs 72.63; p < 0.05), with a large effect magnitude (Cohen's d = 1.3). These outcomes affirm that the ethnomathematics-embedded Android-based m-learning platform constitutes an efficacious and educationally meaningful intervention for cultivating students' mathematical problem-solving proficiency. Nevertheless, further research on a broader scale is warranted to enhance the generalizability of these findings, along with the incorporation of a pretest to more rigorously assess gains and establish stronger causal evidence of the intervention's effectiveness.